Alternative stacking sequences in hexagonal boron nitride. (28th March 2019) - Gilbert, S Matt; Pham, Thang; Dogan, Mehmet; Oh, Sehoon; Shevitski, Brian; Schumm, Gabe; Liu, Stanley; Ercius, Peter; Aloni, Shaul; Cohen, Marvin L; Zettl, Alex
Abstract: The relative orientation of successive sheets, i.e. the stacking sequence, in layered 2D materials is central to the electronic, thermal, and mechanical properties of the material. Often different stacking sequences have comparable cohesive energy, leading to alternative stable crystal structures. Here we theoretically and experimentally explore different stacking sequences in the van der Waals bonded material hexagonal boron nitride (h-BN). We examine the total energy, electronic bandgap, and dielectric response tensor for five distinct high symmetry stacking sequences for both bulk and bilayer forms of h-BN. Two sequences, the generally assumed AA′ sequence and the relatively unknown (for h-BN) AB (Bernal) sequence, are predicted to have comparably low energy. We present a scalable modified chemical vapor deposition method that produces large flakes of virtually pure AB stacked h-BN; this new material complements the generally available AA′ stacked h-BN.